2016
DOI: 10.15226/2374-6874/3/1/00125
|View full text |Cite
|
Sign up to set email alerts
|

Treat or Enhance Cognitive Restraint in Individuals Suffering from Overweight or Obesity? Systematic Revue of the Literature

Abstract: Prior to 1975, the scientific literature mainly used to compare obese with normal-weight subjects or subjects with or without an eating disorder. This period was followed by the emergence of "unrestrained eaters", who have "normal" eating behaviors versus "restrained eaters", who are normal-weight individuals with similar eating behavioral patterns than those of obese people [2]. After this first observation, the definition of a "restrained eater" has developed and came into a consensus: it describes someone w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 66 publications
0
13
0
1
Order By: Relevance
“…Contrary to our hypothesis, we reported that omnivorous diet and cognitive restraint were directly related. Cognitive restraint could lead to an alteration of internal perceptions of hunger and satiety and/or a disinhibition [14], therefore, it can be hypothesized that cognitive restraint in individuals following an omnivorous diet may indicate disordered eating behaviors or maladaptive eating-related attitudes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to our hypothesis, we reported that omnivorous diet and cognitive restraint were directly related. Cognitive restraint could lead to an alteration of internal perceptions of hunger and satiety and/or a disinhibition [14], therefore, it can be hypothesized that cognitive restraint in individuals following an omnivorous diet may indicate disordered eating behaviors or maladaptive eating-related attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Disordered eating is characterized by a disturbed and unhealthy eating pattern that can include restrictive dieting, compulsive eating or skipping meals [13]. Cognitive restraint is defined as the intention to constantly deliberately control food intake in order to maintain or lose weight [14]. This leads to a reduction in the intake of specific macronutrients (e.g., fats or carbohydrates) or types of foods, and not to a reduction in overall caloric intake [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive restraint (CR) is the intention to control food intake in order to maintain or lose weight. [1][2][3] The impact of CR on weight is controversial. Many studies have shown a correlation between weight or body mass index (BMI) and CR, either negative 4,5 or positive.…”
Section: Introductionmentioning
confidence: 99%
“…It explains that restrained eaters develop an alteration in the internal perception of hunger and satiety, disinhibition, emotional dysregulation and a decrease of self-esteem and body satisfaction. 3,[7][8][9] However, many studies have shown the opposite and have therefore promoted the increase of CR to treat overweight and obesity. 10 The question still remains: should we reduce or increase CR in people affected with overweight or obesity?…”
Section: Introductionmentioning
confidence: 99%